A rough comparison of the IETF and ATM service models. - Crowcroft, J. (IEEE Network : the magazine of global information exchange)
There is much in common between the models of traffic management being devised by the IETF and ATM Forum working groups. The authors' goal is to demonstrate that because of this convergence, there are a number of ways that each can take advantage of the other. The authors discuss service models, link sharing, network provision models, traffic service class hierarchies, borrowing and replacement strategies, delays and throughput, ordering and routing with particular application to the Internet